2009
DOI: 10.2337/dc08-1358
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Metabolic Syndrome and Depressive Symptoms in Middle-Aged Adults

Abstract: OBJECTIVE -Although it is possible that the association between depression and the metabolic syndrome is a "two-way street," the metabolic syndrome as a predictor of depression has been little investigated. We examined whether the metabolic syndrome is associated with the onset of depressive symptoms in a cohort of middle-aged British civil servants. RESEARCH DESIGN AND METHODS -Analyses included 5,232 participants(41-61 years of age) from the Whitehall II prospective cohort study. Depressive symptoms were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
128
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 23 publications
16
128
2
2
Order By: Relevance
“…These associations may in part explain why people with psychopathology are at high risk of developing a range of chronic illnesses 9. Metabolic syndrome has been defined as a discrete, binary entity; however, previous research indicates that some components are more strongly associated with psychopathology than others, particularly obesity and dyslipdemia 10, 11, 12. Given these discrepancies between components in the context of psychiatric illness, using a dichotomous definition of metabolic syndrome may not be the strongest way of identifying the nature of associations between psychopathology and metabolic dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…These associations may in part explain why people with psychopathology are at high risk of developing a range of chronic illnesses 9. Metabolic syndrome has been defined as a discrete, binary entity; however, previous research indicates that some components are more strongly associated with psychopathology than others, particularly obesity and dyslipdemia 10, 11, 12. Given these discrepancies between components in the context of psychiatric illness, using a dichotomous definition of metabolic syndrome may not be the strongest way of identifying the nature of associations between psychopathology and metabolic dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with increased risk of subclinical atherosclerosis, cardiovascular disease (CVD), diabetes, and mortality. 1,2 In the past decades, several studies have reported a significant association between the MetS and depression among young 3,4 and older adults. [5][6][7][8][9][10][11] A recent meta-analysis indicates that the relationship between the MetS and depression is probably bidirectional.…”
Section: Introductionmentioning
confidence: 99%
“…28, 29 It has also been reported that metabolic syndrome, in particular obesity, is predictive of depressive symptoms. 30 Although BP measurements at physician check-up were well controlled in both groups, ABPM-measured nocturnal and early morning BP were significantly higher in the anxiety group than in the control group. Further, the relative risk of existing anxiety disorder was significantly higher in the risertype hypertension than that in the dipper-type hypertension.…”
Section: Discussionmentioning
confidence: 99%